The Influence Of Leadership And Job Satisfaction On Turnover Intention At PT. XYZ - Putri, Shafira Salsabilla Kemala; Irbayuni, Sulastri (UNIVERSITAS PAKUAN, 2025)
Turnover intention, or employees' intention to leave the company, is a serious challenge that affects organizational stability and incurs additional costs. This study aims to analyze the influence of leadership and job satisfaction on turnover intention at PT. XYZ, a microfinance institution in East Java that has experienced an increase in turnover rates over the past four years. The results of this study indicate that leadership and job satisfaction contribute to turnover intention. Based on these findings, leaders should be able to make clear decisions and implement a fair promotion system. These improvements are expected to enhance job satisfaction and reduce turnover intention in the future